2018
DOI: 10.1177/0363546517749586
|View full text |Cite
|
Sign up to set email alerts
|

Modified Latarjet Without Capsulolabral Repair in Rugby Players With Recurrent Anterior Glenohumeral Instability and Significant Glenoid Bone Loss

Abstract: In rugby players with recurrent anterior shoulder instability and significant glenoid bone loss, the modified Latarjet procedure without capsulolabral repair produced excellent functional outcomes, with most athletes returning to rugby at their preinjury level of play without recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 27 publications
4
54
0
6
Order By: Relevance
“…Previous authors have also reported high rates of return to sport in collision (G2) athletes, ranging between 65% and 97%, with the Latarjet procedure indicated as a primary surgery. 4,11,21,26,29 However, none of these studies included patients who underwent a revision procedure. Regarding the postoperative level of sport achieved after surgery, only 5% of our patients noticed a decrease in their sports performance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have also reported high rates of return to sport in collision (G2) athletes, ranging between 65% and 97%, with the Latarjet procedure indicated as a primary surgery. 4,11,21,26,29 However, none of these studies included patients who underwent a revision procedure. Regarding the postoperative level of sport achieved after surgery, only 5% of our patients noticed a decrease in their sports performance.…”
Section: Discussionmentioning
confidence: 99%
“…The 14 studies analyzed in the systematic review included 883 patients. [2][3][4][5][6][7][8]10,11,14,[16][17][18]21 The studies were primarily level 3 (n = 4) or level 4 (n = 10) evidence; of the 14 studies, 13 had a MINORS score greater than 80%. Of the studies that reported the participants' sex, the majority were male (88%).…”
Section: Resultsmentioning
confidence: 99%
“…Partial lysis of the coracoid occurs frequently but only rarely leads to persistent apprehension and unsatisfactory outcomes, and no specific management is required unless too proud and/or symptomatic metalwork. 16 , 17 , 18 …”
Section: Discussionmentioning
confidence: 99%